2001
DOI: 10.1097/00007890-200108150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Induction Therapy With Monoclonal Antibodies Specific for Cd80 and Cd86 Delays the Onset of Acute Renal Allograft Rejection in Non-Human Primates1

Abstract: CD80 and CD86 (also known as B7-1 and B7-2, respectively) are both ligands for the T cell costimulatory receptors CD28 and CD152. Both CD80 and CD86 mediate T cell costimulation, and as such, have been studied for their role in promoting allograft rejection. In this study we demonstrate that administering monoclonal antibodies specific for these B7 ligands can delay the onset of acute renal allograft rejection in rhesus monkeys. The most durable effect results from simultaneous administration of both anti-B7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 23 publications
0
67
0
1
Order By: Relevance
“…Alternatively, CD4 blockade could result in suboptimal T cell stimulation upon APC engagement leading to tolerance induction. This idea is supported by the fact that different studies demonstrated tolerance induction after blockade of other co-stimulatory molecules, such as CD28, CD80, or CD86 (38,43,44).…”
Section: /Cd8mentioning
confidence: 92%
“…Alternatively, CD4 blockade could result in suboptimal T cell stimulation upon APC engagement leading to tolerance induction. This idea is supported by the fact that different studies demonstrated tolerance induction after blockade of other co-stimulatory molecules, such as CD28, CD80, or CD86 (38,43,44).…”
Section: /Cd8mentioning
confidence: 92%
“…by our group and others (10)(11)(12)(13)(14)(15)(16). Belatacept is a first-in-class selective costimulation blocker and is clinically indicated as a CNI inhibitor substitute with mycophenolate mofetil and steroids after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of monoclonal antibodies against CD80 and CD86 was investigated in the NHP renal allograft model (Kirk et al 2001b). Monotherapy with either of these antibodies produced only modest increases in time to rejection.…”
Section: Costimulation Blockadementioning
confidence: 99%